Effects of environmental air pollution on pulmonary function level of residents in Korean industrial complexes - Hong, Eunju; Lee, Seokwon; Kim, Geun-Bae; Kim, Tae Jong; Kim, Hyoung-Wook; Lee, Kyoungho; Son, Bu-Soon (International Journal of Environmental Research and Public Health, 2018)
This study aims to identify environmental air pollution adversely affecting pulmonary function among a community-based general population living in Korean industrial complexes. A total of 1963 residents participated in a pulmonary function test (PFT). The sample population consisted of an exposed group (n = 1487) living within a radius of 5 km of industrial complexes and a control group (n = 476) living over a radius of 10 km from the industrial complexes in Gwangyang and Yeosu cities. PFT results were calculated for each resident of the study population. On-site questionnaire surveys with face-to-face interviews were also conducted to collect more detailed information on personal lifestyles, medical history, exposure to air pollution, and respiratory disease and related symptoms. A total of 486 measured samples were collected by eight automated air-monitoring stations installed in four counties of Gwangyang and four counties of Yeosu in South Korea from January 2006 to February 2007. Mean levels of SO2 (0.012 ppm), CO (0.648 ppm), NO